PERLINDUNGAN TERHADAP ANAK KORBAN KECANDUAN GAME ONLINE: Studi Kasus di Kota Makassar - Arianto, Saeful; Samin, Sabri; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Children are an integral part of the younger generation and the potential of the nation's human resources in the future. Efforts to foster and protect children are a shared responsibility in ensuring physical, and mental growth and development. This research is a qualitative research field. The results showed that regulatively, the Makassar City Government already has regulations related to child protection, namely Makassar City Regional Regulation Number 5 of 2018 concerning Child Protection, but technically, the regulation has not regulated the protection of children from online game addiction. Efforts to protect children from the negative influence of online games are not only the responsibility of the government, but the role and commitment of the family and the environment are also determining factors, especially the presence of online games related to information technology which has become a primary need.